Strengthening parenting in conflict-affected communities: development of the Caregiver Support Intervention - Kenneth E. Miller; Heba Ghalayini; Maguy Arnous; Fadila Tossyeh; Alexandra Chen; Myrthe van den Broek; Gabriela V. Koppenol-Gonzalez; Joy Saade; Mark J.D. Jordans (Cambridge Prisms: Global Mental Health, 2020)
AbstractBackgroundThere is robust evidence that compromised parenting, stemming from persistently high stress, mediates the impact of war and displacement on children's mental health and psychosocial wellbeing. Parenting interventions generally prioritize the acquisition of parenting knowledge and skills, while under-attending to parental stress and distress. This paper describes the development of the Caregiver Support Intervention (CSI), a nine-session group intervention for conflict-affected parents of children aged 3–13, that aims to strengthen parenting both indirectly, by lowering stress and improving psychosocial wellbeing among parents, and directly, by increasing knowledge and skill related to positive parenting.MethodsWe describe the multi-phase, iterative process by which we developed the CSI, and illustrate the essential role of community input in shaping the intervention and strengthening its cultural fit and perceived usefulness. We used focus group data from participants in successive cycles of implementation, feedback, and revision, as well as quantitative data and expert consultation to develop a culturally and empirically grounded intervention.ResultsThis mixed-method, iterative approach to intervention development enabled us to develop a psychosocial intervention for conflict-affected caregivers that is feasible, acceptable, and perceived by participants as useful in addressing their own wellbeing and their parenting. Focus group data support the underlying model in which caregiver wellbeing powerfully influences parenting.ConclusionsPrograms aimed at strengthening parenting in conflict-affected communities should substantively address caregiver wellbeing. An iterative approach incorporating community feedback can help ensure intervention acceptability and feasibility. We also illustrate the feasibility of involving men in parenting interventions.